POLA PENGOBATAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PEDIATRIK RAWAT INAP DI PUSKESMAS SAWANG KABUPATEN ACEH UTARA - Eva DIansari Marbun; Modesta Harmoni Br Tarigan; Erlita Utari (FORTE JOURNAL, 2022)
Acute Respiratory Infection (ARI) is a disease that is often experienced by toddlers with symptoms such as cough, runny nose and fever for the last 2 weeks. ARI can be caused by one of the factors, namely internal/environmental factors. The purpose of this study was to determine whether the treatment therapy for Pediatric ARI at the Sawang Health Center had met WHO standards or not. This study is a descriptive observational research method that aims to describe research problems that occur based on the characteristics of patients with pediatric ARI. This research was conducted from July-September 2020, while correspondent medical record data was taken in April-June 2020. while respondents who met the inclusion criteria were as many as 50 respondents. The results showed that of the 50 respondents who had ARI patients, the most experienced ARI based on gender were male (54%), and pediatric 4-7 years (56%). The class of antibiotics most often used in ARI therapy is the penicillin group (Amoxicilin) ​​(32%) compared to other groups, while additional symptomatic drugs to relieve symptoms caused by ARI that are often used are analgesic drugs (paracetamol) (100%). The results of the study based on statistical analysis tests obtained sig 0.005 results, it can be concluded that there is a significant relationship between all criteria (age, gender, use of antibiotic therapy drugs and use of symptomatic therapy drugs) and the pattern of ARI treatment at the Sawang Health Center, North Aceh Regency.